Perangkat Pembelajaran Matematika Berbasis Guided Discovery untuk Kemampuan Pemecahan Masalah Peserta Didik Sekolah Dasar - Fitriadi Fitriadi; Yanti Fitria (Universitas Negeri Padang, 2022)
This study aims to develop a mathematics learning tool based on the guided discovery method in order to improve the problem-solving abilities of fourth-grade elementary school students. The type of research is development research with the Plomp model which consists of three stages, namely preliminary analysis, prototype development, and assessment. The results showed that the learning device was declared to be very valid with a score of 3.67, very practical with a score of 97.3, and effective with an average student learning outcome assessment of 76.23 and was above the KKM. Thus, this Mathematics learning tool with the Guided Discovery Model is highly recommended and suitable for use in elementary schools.